Construction Of Non-Type Dayah And Teaching Call With Qur'an Distribution In Lhokseumawe City And North Aceh District, Aceh Province - Erman, Nilam; Winario, Mohd; Meilany, Merry; Zulkifli, Zulkifli (Journal of Community Sustainability, 2024)
The construction of non-type dayah and recitation halls with the distribution of the Koran in Lhokseumawe City and North Aceh Regency, Aceh Province aims to increase access and quality of Islamic religious education in Aceh. The main objective of this program is to strengthen the Islamic education infrastructure with a focus on developing non-type pesantren and prayer halls as centers of sustainable religious learning. The methods used include location identification, fund collection, infrastructure planning, selection of teaching staff, and coordination with local government and local communities. The expected results of this program are the creation of a conducive religious education environment, increased understanding and practice of Islamic teachings in the local community, as well as becoming a model for the development of Islamic religious education in other areas. With full support from the local government and community, it is hoped that this program can have a significant positive impact on the progress of Islamic religious education in Aceh.